Personality matching internship placement system (PMIPS) among students of a public higher learning institution / Zainuddin Zakaria …[et al.] - Zakaria, Zainuddin; Mohamed, Hasiah; Jusoh, Zuraini; Ahmad, Zuriyati; Kamaludin, Mohd Ariff; Ismail, Nur Zaheerah (Research Management Centre (RMC), 2020)
The Personality Matching Internship Placement System (PMIPS) is a web-based system designed to assist students find a place for their industrial training using their personality scores as the basis for choosing the most suitable organisations or departments. This system will help them to choose the right organisations that match the organisation’s needs and requirement. The Adapted Waterfall model was used to develop the PMIP system. The evaluation of PMIPS is conducted once the development is completed. There are six constructs used for the evaluation purposes and 30 respondents were involved. The six constructs are ease of use, satisfaction, efficiency, consistency, user interface and usability. Respondents are required to use the system and then they were asked to answer the questionnaire given. As a result of the evaluation, the highest mean score is for the efficiency construct, 4.63(SD=0.49). The results show that the respondents perceived that it is efficient for them to use the system because they are able to see the results of their personality and which company is suitable for their internship placement. Future enhancement for the system includes functions that match the students’ personality with the specific job requirement.